Problematika Pembelajaran Daring pada Masa Pandemi Covid 19 di Sekolah Dasar - Musbaing (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2022)
This study aims to find out the problems of courageous learning during the Covid 19 pandemic in thematic learning in class IV SD Inpres Bakung 2 Makassar City. This research was conducted at SD Inpres Bakung 2 Makassar City. Using a qualitative approach to the type of descriptive research. Data collection techniques are observation, interviews and documentation. The subjects in this study were fourth grade teachers of SD Inpres Bakung 2 Makassar City, while the data sources consisted of main informants and supporting informants. Activities in data analysis are data reduction, data presentation, conclusion drawing/verification. To test the validity of the data include source triangulation, technical triangulation, and time triangulation. The results of this study indicate that the problem of online learning in thematic learning is the teacher's lack of understanding about learning innovation and the lack of creativity of a teacher in providing media that is able to attract and arouse student learning motivation. During the learning process, the teacher uses a whatsapp group by sending photos only for assignments related to the material being studied. As for efforts to overcome this problem, teachers must have the awareness to provide interesting media, and create active, innovative, creative, and effective classroom strategies.